HEDONIC COMSUMPTION BEHAVIORS: A COMPARATIVE ANALYSIS OF THE EFFECTS OF DEMOGRAPHIC FACTORS ON HEDONIC SHOPPING BEHAVIOURS OF THE STUDENTS AT KAHRAMANMARAŞ SÜTÇÜ İMAM UNIVERCITY AND ADIYAMAN UNIVERCITY - Arif YILDIZ (Fırat University, 2019)
The aim of this study was to measure the effects of the consumers’ hedonic (hedonist) shopping behaviors and socio-demographic characteristics on “hedonism”, “hedonic (hedonist) consumer behaviors” and “utilitarian consumer behaviors” with giving information about these behaviors. The Article consists of two parts. First, information about hedonism was given in the first part in which theoretical framework was formed. ''Hedonism" which is described as a philosophical view defends that the pleasure is an absolute good sense, human actions should be planned to provide a ultimate pleasure and the most appropriate behavior trend is choosing continuous pleasure, and recently it has been defined as one of the important issues especially in the marketing area. Utilitarian and hedonic consumer behaviors at shopping were explained in the later part of the study. Causes of hedonic consumption were explained in the last part of the theoretical framework. These factors which constituted the scale of the survey forms are listed as adventurous shopping, social shopping, shopping for relax relaxing, shopping for getting idea, shopping for making somebody happy and shopping for value. In the second part of the study which includes the application; the surveys which have been made to reveal the causes pushing the students of Kahramanmaraş Sütçü imam Univercity and Adıyaman Universities to hedonic consumption behavior and to compare the effects of demographic factors on hedonic shopping behaviors of the students of these two univercities have been analyzed and the results of these analysis were identified. The main reason for preferring these two universities is that the student profile is different between them especially in terms of socio-demographic factors. As a result, the data obtained at the end of the study confirmed this idea.